Dielectric properties of Pb(Zr1/2Ti1/2)O 3-Pb(Zn1/3Nb2/3)O3 ceramics under compressive stress - Rattikorn Yimnirun (2018)
Effects of compressive stress on the dielectric properties of PZT-PZN ceramics with a formula (1-x) Pb(Zr1/2Ti1/2)O3-xPb(Zn1/3Nb2/3)O3or (1-x) PZT-(x)PZN(x = 0.1-0.5) were investigated under stress up to 230 MPa. The experimental results revealed that the superimposed compression stress had pronounced effects on both the dielectric constant and the dielectric loss tangent of PZT-PZN ceramics. In addition, the dielectric properties were considerably lowered after a stress cycle. The observations were mainly interpreted in terms of domain switching through non-180° domain walls, clamping of domain walls, de-aging, and the stress induced decrease in switchable part of spontaneous polarization.